THE PROFILE OF STUDENTS' SCIENCE PROCESS SKILL IN LEARNING HUMAN MUSCLE TISSUE EXPERIMENT AT SECONDARY SCHOOL - Shofwa Widdina, - (2017)
Science process skills is a human basic form of learning process, it is not used only by the scientis in the process of their discovery, but also by the people as tools to understand information about the world. The aim of this study was to profile srudents' basic science process skills, to profile students' integrated science process skills, and the profile of students' science process based on gender. In gaining the data this study use observation method in students laboratory activity. The results of study indicated that students' basic science and integrated science process skills were most indicators science process used in this study categorized in high category. There is no significant differences in the profile students science process skills based on gender other than male students did outperformed female students.---- Keterampian Proses Sains adalah dasar dalam proses pembelajaran, tidak hanya digunakan oleh saintis untuk membantu prosess penemuan mereka, tetapi juga digunakan oleh orang-orang sebagai alat untuk memahami informasi tentang dunia. Tujuan dari penelitian ini menggambarkan profil kemampuan dasar keterampilan proses sain siswa, menggambarkan profil kemampuan lanjutan keterampilan proses sain siswa, dan gambaran proses sains siswa berdasarkan gender. Untuk mendapatkan data yang diinginkan menggunakan metode observasi dalam kegiatan laboratory. Hasil dari penelitian menunjukkan kemampuan dasar proses sains siswa dan kemampuan lanjutan proses sains siwa disetiap indicaator adalah tinggi. Selain siswa laki-laki lebih unggul di beberaa proses sains tidak ada perbedaan yang mencolok dalam keterampilan proses sains siswa berdasarkan gender.